EVR-CB-004: An Inflated Hot Subdwarf O Star plus Unseen WD Companion in a Compact Binary Discovered with the Evryscope - Ratzloff, Jeffrey K.; Kupfer, Thomas; Barlow, Brad N.; Schneider, David; Marsh, Thomas R.; Heber, Ulrich; Corcoran, Kyle A.; Bauer, Evan; Hämmerich, Steven; Corbett, Henry T.; Glazier, Amy; Howard, Ward S.; et al. (Astrophysical Journal, 2020)
We present the discovery of EVR-CB-004, a close binary with a remnant stellar core and an unseen white dwarf (WD) companion. The analysis in this work reveals that the primary is potentially an inflated hot subdwarf (sdO) and more likely is a rarer post-blue horizontal branch (post-BHB) star. Post-BHBs are the short-lived shell-burning final stage of a blue horizontal star or hot subdwarf before transitioning to a WD. This object was discovered using Evryscope photometric data in a southern all-sky hot subdwarf variability survey. The photometric light curve for EVR-CB-004 shows multicomponent variability from ellipsoidal deformation of the primary and Doppler boosting, as well as gravitational limb darkening. The binary EVR-CB-004 is one of just a handful of known systems and has a long period (6.08426 hr) and large-amplitude ellipsoidal modulation (16.0% change in brightness from maximum to minimum) for these extremely close binary systems, while the properties of the primary make it a truly unique system. It also shows a peculiar low-amplitude (less than 1%) sinusoidal light-curve variation with a period that is a 1/3 resonance of the binary period. We tentatively identify this additional variation source as a tidally induced resonant pulsation, and we suggest follow-up observations that could verify this interpretation. From the evolutionary state of the system, its components, and its mass fraction, EVR-CB-004 is a strong merger candidate to form a single high-mass (1.2M) WD. It offers a glimpse into a brief phase of remnant core evolution and secondary variation not seen before in a compact binary.
CRIS-Team WoS Importer:2020-10-30